Defending AI Sentinels: A Multi-Layered Runtime Security Architecture for Generative AI in AIOps - Ayobami E. Mesioye; Oladapo O. Adeduro; Johnson B. Oluwagbemi (PT. Teknologi Futuristik Indonesia, 2026)
The rapid integration of Generative AI into Automated IT Operations (AIOps) has introduced